Dietary and drinking water intake of essential trace elements in a typical Kashin-Beck disease endemic area of Tibet, China - Xinjie Zha; Jialu An; Xue Gao; Yuan Tian (Environmental Health, 2022)
Abstract Background Essential trace elements (ETEs), such as copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), selenium (Se), zinc (Zn), are very important elements for human health. Methods In this study, 89 drinking water samples and 85 highland barleys were collected from 48 villages in 11 townships, and the average daily dose (ADD) of ETEs were calculated, in addition, health effects of ETEs to rural residents in Luolong County, a typical Kashin-Beck disease (KBD) endemic area in Tibet, were assessed. Results The mean concentrations of Cu, Fe, Mn, Mo, Se, Zn in drinking water were 0.278 ± 0.264 μg·kg−1, 0.766 ± 0.312 μg·kg−1, 0.411 ± 0.526 μg·kg−1, 0.119 ± 0.223 μg·kg−1, 0.155 ± 0.180 μg·kg−1, and 0.804 ± 1.112 μg·kg−1, respectively; and mean concentrations of Cu, Fe, Mn, Mo, Se and Zn in highland barley were 3.550 ± 0.680 mg·kg−1, 81.17 ± 38.14 mg·kg−1, 14.03 ± 1.42 mg·kg−1, 0.350 ± 0.200 mg·kg−1, 0.0028 ± 0.0056 mg·kg−1, and 23.58 ± 3.10 mg·kg−1, respectively. The ADD of Cu in the study area was appropriate; the ADD of Fe and Mn in each township were higher than the maximum oral reference dose recommended by the National Health Commission of China, indicating that Fe and Mn had non-carcinogenic health risks; the ADD of Mo and Zn in 36.36% and 54.55% of the townships exceeded the maximum oral reference dose; and 72.73% of the townships had insufficient ADD of Se. The ADD of Mo, Cu and Se in different townships was significantly correlated with the prevalence of KBD. Conclusions Therefore, in order to prevent and control the prevalence of KBD and ensure the health of local residents, it is necessary to reduce the intake of high concentrations of Fe, Mn and Zn in diet, as well as increase the intake of Mo, Cu, especially Se. Graphical abstract